Empirical study of the 30-s chair-stand test as an indicator for musculoskeletal disorder risk of sedentary behaviour in Japanese office workers: a cross-sectional empirical study. Issue 1 (22nd March 2021) - Arimoto, Azusa; Ishikawa, Shoko; Tadaka, Etsuko
Abstract : Objectives: Sedentary behaviour among office workers and the risk of adverse health outcomes are public health problems. However, risk indicators for these outcomes require invasive biochemical examination. A proactive screening tool using a non-invasive, easy-to-use method is required to assess the risk focused on musculoskeletal health for primary prevention. However, middle-aged adults have insufficient awareness of musculoskeletal disorders. This study examined to determine whether the 30-s chair-stand test (CS-30) can be used as a proactive screening index for musculoskeletal disorder risk of sedentary behaviour in office workers. Design: Cross-sectional study using self-administered questionnaires and physical measurements. Setting: Four workplaces located in a metropolitan area of Japan. Participants: 431 Japanese office workers aged 20–64 years. 406 valid sets of results remained (valid response rate: 94.2%). Primary and secondary outcome measures: Musculoskeletal function was measured using the CS-30, quadriceps muscle strength. Receiver operating characteristic curve analysis was used to determine the sensitivity, specificity and optimal cut-off value for the CS-30. The risk of future incidence of musculoskeletal disorders was calculated using current quadriceps muscle strength. Results: In total participants, 47.0% were male and the mean sitting time in work duration was 455.6 min/day (SD=111.2 min). The mean lower limb quadriceps muscle strength was 444.8 N (SD=131.3 N). For the optimum cut-off value of 23 on the CS-30 for all participants, sensitivity was 0.809 and specificity was 0.231. For men, the optimum cut-off was 25, with a sensitivity of 0.855 and a specificity 0.172. For women, the optimum cut-off was 21, with a sensitivity of 0.854 and a specificity 0.275. Conclusions: Sensitivity was high, but specificity was insufficient. The CS-30 may be a potential proactive screening index for musculoskeletal disorder risk of sedentary behaviour, in combination with other indicators.